PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO FOOD PLATING SEBAGAI SUMBER BELAJAR MAHASISWA - Rina Setyaningsih; Siti Mariah (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2023)
The research objectives were: (1) to describe the development of learning media for food plating videos; (2) to test the validation of food platting video; and (3) knowing the effectiveness of developing food plating video learning media. This type of research is the development of the ADDIE model. Data analysis uses descriptive, qualitative, quantitative and inferential statistical analysis (-t test). The results showed (1) developing food plating video learning media using the ADDIE development model : analysis, design, development, implementation, evaluation.  (2) The development of learning media for this food plating video is valid based on material experts 98.20% of the category is very good, media experts 96.50% of the category is very good, individual trials of 94.54% of the categories are very good, small-scale tests are 93.21% with very good categories, field scale tests of 90.00% of the categories are very good.  (3) The effectiveness of the development of food plating video learning media effectively increases practical learning (tcalculate = 16,800 > ttable = 2,000 at a significance level of 5%).